Application of 13 loci STR multiplex for cannabis sativa genotyping. Issue 1 (December 2019) - Fabbri, M.; Frisoni, P.; Marti, M.; Talarico, A.; Bonato, O.; Coppone, M.; Lucenti, E.; Gaudio, R.M.; Neri, M.
Abstract: Our work describes an application of a STR multiplex systems for 13 loci, previously developed and validated in our laboratory following international guidelines, on 4 cannabis specimens seized by Anti-Narcotic Italian Police. STR loci were chosen from the set of publicly available STRs for cannabis sativa and among the highly polymorphic available in literature. Gas chromatography with a flame ionization detector (GC-FID) and gas chromatography-mass spectrometry (GC–MS) analysis revealed and confirmed four comparable molecular spectrums, approximatively descriptive of the same plant/seizure origin. Due to these uncertain results, investigative authorities approved the genetic analysis. DNA profiling allowed to identify the same genetic profile and consequently the same origin and individualization of the specimens analysed.